KATA-KATA TABU PADA BAHASA DAERAH MEDAN - Syahdani, Ruri Alfia (Universitas Harapan Medan, 2023)
This research aimed to find out the types of taboo words, described the meaning of taboo words and each types to find the results of the percentage and dominant of taboo words. The research method used in completing this thesis was descriptive qualitative approach. In analyzing the data, theory of Wardhaugh (2006) was used to classifies the categories of taboo words and types of the informants utterances. This research used the method of interviews by the informants as sociolinguistics approach and use a field research in Medan local language. The result of this research showed that there were 14 data that has been classifies into the types of taboo words where the dominant was death and excretion (28,58%) with each 4 (four) data. Next, followed by sex term with 3 (three) data, body function with 3 (three) data, religious matter with nol data, and politics with nol data.